Influence of Pyrolysis Conditions on the Adsorbent Properties of Hazelnut Shell Biochar to Remove Paracetamol, Amoxicillin, and Triclosan - Villamar-Ayala, C; Madariaga-Segovia, P (Elsevier Ltd, 2025)
This study optimized the production of biochar from hazelnut shells for the adsorption of paracetamol, amoxicillin, and triclosan from water. Biochar was produced under 27 conditions (temperature: 500–900 °C, time: 0.5–2 h, particle size: 150–2000 μm). Physicochemical and instrumental analyses, as well as batch adsorption tests, characterized the samples. Temperature (900 °C) is the most significant factor influencing biochar properties and adsorption performance. Adsorption data fitted well with heterogeneous isotherm models, including the Sips model and multilayer/monolayer models. The maximum adsorption capacities for paracetamol, amoxicillin, and triclosan were 19.973, 2.992, and 2.678 mg/g, respectively. Biochar-based adsorption systems with water treatment applications will be scaled. © 2025